USING A PHYSICAL ACTIVITY WEARABLE TRACKER: OLDER LATINOS' PERCEPTIONS. (11th November 2018) - Marques, I; Cantoral, J; Guzman, J; Moraes Balbim, G; Marquez, D
Abstract: By 2050, more than 21 million older Latinos are expected in the U.S. The Latino population has been gaining access to technologies; however, Latinos have low levels of leisure-time physical activity (PA). The purpose of this study was to identify older Latinos' perceptions of tracking their PA during an intervention. Participants were enrolled in the 16-week BAILA TECH program that includes the BAILAMOS© dance program, the use of a PA wearable tracker and associated mobile application, text messages, and mobile technology education classes. Classes were held twice a week for 2 hours each session. Focus groups were held at the beginning of each month of the program. Discussions were transcribed in Spanish, translated into English, and thematic analysis was conducted. Discussion 1 was held after 2 weeks of wearing the PA tracker, and participants reported questions with overall use of the PA tracker (e.g., how to charge). Discussion 2 was held during week 6, and participants had more specific questions about the PA tracker (e.g., reminders to move). Discussion 3 was held during week 10, and participants reported exploring various features on the mobile application. Discussion 4 was held during week 14, and participants reported that the PA tracker motivated them to achieve their daily goal steps. Future interventions should incorporate mobile health educational classes to enhance participants' engagement with the mobile technology.